THE USE TECHNOLOGY BASED ON ARTIFICIAL INTELLIGENCE IN ENGLISH TEACHING AND LEARNING) - Tira Nur Fitria (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2021)
Artificial Intelligence (AI) is a human intelligence simulation based on computers and designed to function as human beings. AI is one of the drivers of the 4.0 industrial revolution to facilitate education in teaching and learning. This research is to know the role of AI in ELT and to investigate AI technologies in ELT. This is library research. The result shows that AI offers a good learning atmosphere for English learning. It has considerable ability to create a personalized atmosphere in which learners use their senses to concurrently exercise English skills depending on their current level of English, vocational needs, or interests. AI provides a real simulation dialog platform such as spoken English and increases practical skills such as written. It increases the practice of students’ capacity and optimizes the teaching impact of English in ELT. Learning English become easier with the development of technology and platforms. AI’s technology offers the opportunity to improve English language skills. The existence of various kinds of learning technology makes it easier for students to understand English. Many choices of ELT applications are based on AI technology that can be used by the students. These technologies as smart machines that think and behave like people with the ability to simulate intelligence and make decisions identical to human reasoning through a process both computers and cell-phones such as Google Translate, Text to speech (TTS), English Able, Orai, Elsa, Chatbot, Duolingo, Neo platforms, and many more.